Sociomathematical and Ethnomathematical Exploration of Mathematical Literacy Junior High School Students - Irmayanti Irmayanti; Suradi; Muhammad Izzad Kaisar; Fitriani Fitriani (Universitas Islam Ahmad Dahlan (UIAD), 2026)
This research is a systematic literature review (SLR) which aims to analyse the sociomathematical and ethnomathematical exploration of mathematical literacy among junior high school (SMP) students. The study examines national and international articles relevant to the topics of sociomathematics, ethnomathematics and mathematical literacy. A total of 46 articles were identified from various databases, such as Scopus, ERIC, Google Scholar and Garuda. Through a systematic screening process, 33 articles published between 2023 and 2025 were selected for in-depth analysis. The results show that sociomathematical and ethnomathematical approaches play an important role in encouraging meaningful social interaction and the negotiation of mathematical meaning. They also promote the active involvement of students in relating mathematical concepts to daily life. Integrating local cultural contexts has been shown to strengthen conceptual understanding, increase a sense of belonging to the learning process, and foster awareness of social values in mathematics. However, the results also indicate that research integrating sociomathematics, ethnomathematics and mathematical literacy holistically remains limited, particularly at junior high school level. Therefore, there is a need to develop a learning design that combines social, cultural, and conceptual dimensions of mathematics learning. This study recommends socio-cultural learning models as an innovative way to strengthen 21st century mathematical literacy by associating cultural contexts, social practices, and meaningful mathematical understandings.